When and Why Consumers “Accidentally” Endanger Their Products - Shani, Yaniv; Appel, Gil; Danziger, Shai; Shachar, Ron (Management Science, 2020)
In this article, we examine whether consumers may “accidentally” endanger a product they own when a new version of the product is introduced. We propose that owners endanger their product when they want to upgrade to a new version but have difficulty justifying the upgrade and that owners find justification more difficult when a new version offers an improved design but does not offer a significant technological improvement. Owners endanger their product hoping that it will be fortuitously damaged. Product damage provides owners with a good reason to upgrade. Focusing on iPhone as a case study, field data and experiments provide evidence for product endangering, and they support the role of justification in three ways. First, as hypothesized, endangering occurs when the new product offers an improved design but does not offer a significant technological improvement. Second, owners are less likely to endanger a product that is under warranty; therefore, damage to it will not enable upgrading. Third, owners are more likely to endanger their product when their justification concerns are heightened. This paper was accepted by Yan Chen, decision analysis.